Utilizing Semantic Mapping to Enhance Students' Understanding in Reading - Sundari, Ari Gusti; Daulay, Sholihatul Hamidah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
Reading is a fundamental skill in English learning; nevertheless, many English learners encounter challenges in comprehending English texts. Thus, providing students with effective reading strategies is essential. This study aimed to evaluate the effect of semantic mapping on improving students' reading comprehension. Using a quasi-experimental design, the research targeted first-semester students from the Tarbiyah Faculty and Teacher Training at the English Department UINSU, who were specifically selected as participants. Data was gathered using the TOEFL reading test, and analysis was performed with SPSS version 21 IBM, including frequency, mean score, normality test, and nonparametric tests (Mann-Whitney U test and Wilcoxon test). The findings showed that using semantic mapping as a teaching method significantly improved students' reading performance. The Mann-Whitney U test revealed a notable difference between the mean scores of the experimental group using semantic mapping and the control group without it (42.3 > 32.3). Furthermore, the Wilcoxon test indicated a significant improvement in the experimental group's scores from the pretest (29.5) to the post-test (42.3). In summary, semantic mapping seems to enhance students' reading comprehension.